Improved interfacial performance of bamboo fibers/polylactic acid composites enabled by a self-supplied bio-coupling agent strategy. (20th December 2022) - Fang, Xiaoyang; Li, Yanchen; Zhao, Junqi; Xu, Jianuo; Li, Chuanchuan; Liu, Jiaxun; Liu, Yi; Guo, Hongwu
Abstract: Natural fibers reinforced biopolymer composites (NFRBC) are attractive alternatives to petroleum-based plastics due to their renewability, carbon neutrality, and degradability. However, the incompatibility between the fibers and the polymer matrix has long been considered a challenging issue that prevents NFRBC from being widely used. The most common approach to overcome this problem is through surface modification of natural fibers, which always involve toxic or unsustainable reagents. Here, we focused on a cleaner and more sustainable strategy to address this issue. By using the deep eutectic solvent system, we successfully deposited a layer of lignin on the surface of the bamboo fibers to serve as a bio-coupling agent, self-supplied from the bamboo fibers rather than using exogenous lignin, petroleum-based coupling agents, or toxic reagents, which is more resource and energy efficient. The obtained bamboo fibers could simultaneously achieve interface compatibility enhancement and polylactic acid (PLA) matrix toughening. The PLA-based composites exhibited clearly better performance, including mechanical strength (the bending strength, tensile strength, impact strength, and elongation-at-break increased by 33.10%, 72.29%, 44.38%, and 40.80%, respectively), thermal stability (the Tonset increased from 290.6 °C to 331.9 °C), and water resistance (the water absorption decreased from 12% to 8%). Overall, with the self-supplied bio-coupling agent applied, this work suggests a new way toward developing more sustainable, stronger, and cleaner bio-composites. Highlights: Liberating the lignin from the interior to the surface of the bamboo fibers to act as a bio-based coupling agent. Drying the obtained fibers at 150 °C leads to a further improvement of the strength of PLA-based composites. High thermal stability and water resistance were also achieved with the proposed strategy. All the materials involved in this paper are non-toxic, sustainable, abundant, and ecofriendly.